The Effect of Exercise with Ladder Drill Slaloms and Carioca on Speed and Agility - Alviana, Silva Icha; Mintarto, Edy; Hariyanto, Agus (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study is to analyze about: (1) the effect of slaloms ladder drill exercises on speed and agility; (2) the effect of carioca ladder drill training on speed and agility; (3) the difference between the effect of the Carioca ladder drill and the Carioca ladder drill on speed; (4) differences in the influence of carioca ladder drill and carioca ladder drill on agility. This type of research is quantitative with quasi-experimental methods. The research design used is maching only design and data analysis using t-test and ANOVA. Retrieval of data using a sprint 30 meters to measure speed and agility t-test to measure agility at the time of the pretest and posttest. The results showed that the difference between the pretest and posttest of each group were: (1) experimental group I for speed = 0.577 and agility = 0.663 (2) experimental group II for speed = 0.81 and agility = 0.757 (3) control group for speed = 0.122 and (4) control group for agility = 0.029. Based on the above analysis, it can be concluded that there is an increase in speed and agility for each group after being given the Ladoca drill ladder drill and carioca ladder drill seen from the t-test. In addition, through the ANOVA test, there are differences in speed in the two types of exercise. Carioca drill ladder increases speed compared to slaloms. While in agility there is no difference between ladder drill slaloms and carioca, but both groups have a better influence than the control group.